The Influence of Leadership Style and Work Discipline on Employee Performance at PT. Bambu Cemerlang (Lazada) Hub Sumur Batu - Fortega, Glen Fortuna Dela; Iqbal, Teuku M.; Amzul, T. Alexander A. (Fin Sinergy: Jurnal Manajemen Keuangan, 2023)
This research examines the influence of leadership style and work discipline on employee performance within PT. Bambu Cemerlang (LAZADA). In organizational contexts, human factors are paramount, driving all activities towards achieving goals. Effective management hinges upon knowledgeable and skilled employees operating within suitable leadership frameworks. Leadership style, defined as the behavioral norm guiding influence over others, significantly impacts organizational success. Similarly, work discipline fosters order and efficiency, crucial for goal attainment. Through quantitative analysis utilizing SPSS software, data from interviews, questionnaires, and observations were analyzed. Results indicate that both leadership style and work discipline significantly affect employee performance. The combined effect of these variables contributes substantially to employee performance, as evidenced by a coefficient of determination of 62.8%. However, 37.2% of performance variation remains unexplained, suggesting the presence of other influencing factors. This study provides empirical evidence supporting the importance of leadership style and work discipline in enhancing employee performance. The findings offer valuable insights for human resource development strategies and contribute to the management literature.